2012
DOI: 10.1186/1471-2164-13-287
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome characterization via 454 pyrosequencing of the annelid Pristina leidyi, an emerging model for studying the evolution of regeneration

Abstract: BackgroundThe naid annelids contain a number of species that vary in their ability to regenerate lost body parts, making them excellent candidates for evolution of regeneration studies. However, scant sequence data exists to facilitate such studies. We constructed a cDNA library from the naid Pristina leidyi, a species that is highly regenerative and also reproduces asexually by fission, using material from a range of regeneration and fission stages for our library. We then sequenced the transcriptome of P. le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 90 publications
1
26
1
Order By: Relevance
“…Most isotigs (93.24%) were > 500 bp in length, and 40.64% of them were > 1000 bp. The average length of the Liaoning cashmere goat isotigs (1,011 bp) was longer than most of those assembled in other non-model organisms, such as Melitaea cinxia (197 bp) [30], Acropora millepora (440 bp) [31], P. contorta (500 bp) [32], Pristina leidyi (707 bp) [33], and Megalobrama amblycephala (730 bp) [19], but they were shorter than the average length in Junco hyemalis (1,248 bp) [34]. About 112,148 (18.70%) reads did not assembled into isotigs.…”
Section: Resultsmentioning
confidence: 99%
“…Most isotigs (93.24%) were > 500 bp in length, and 40.64% of them were > 1000 bp. The average length of the Liaoning cashmere goat isotigs (1,011 bp) was longer than most of those assembled in other non-model organisms, such as Melitaea cinxia (197 bp) [30], Acropora millepora (440 bp) [31], P. contorta (500 bp) [32], Pristina leidyi (707 bp) [33], and Megalobrama amblycephala (730 bp) [19], but they were shorter than the average length in Junco hyemalis (1,248 bp) [34]. About 112,148 (18.70%) reads did not assembled into isotigs.…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression profiling in anterior regenerating segments of Perionyx excavatus also yielded several novel ESTs, involved in regeneration[ 71 ]. Transcriptomics analysis of a mixed-stage sample of regeneration and fission in Pristina leidyi has also been recently attempted [ 72 ]. In our study, we found that 315 amongst the 9,645 genes upregulated during regeneration had no known ortholog.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging genomic methods will be useful to understand this process. By sequencing genomes and transcriptomes, genes involved in regeneration can be identified (Bhambri et al, 2017;Myohara et al, 2006;Nyberg et al, 2012), thereby opening up the possibility of a functional characterization, e.g., by CRISPR or RNAi methods (Boettcher & McManus, 2015). Different studies of annelid regeneration identified the expression of genes such as engrailed, wingless (Wnt), orthodenticle homologs, markers of germline cells (e.g.…”
Section: Reports Of Bifurcated Patterns In Regeneration Are Known Frommentioning
confidence: 99%